Genome Sequencing of West Nile Virus from Human Cases in Greece, 2012 - Riccardo Cusinato; Giorgio Palù; Theodolinta Testa; Giulia Masi; Thomas Martello; Laura Squarzon; Enrico Lavezzo; Elisa Franchin; Anna Papa; Monia Pacenti; Luisa Barzon (Viruses, 2013)
A West Nile Virus (WNV) lineage 2 strain, named Nea Santa-Greece-2010, has been demonstrated to be responsible for the large outbreaks of neuroinvasive disease (WNND) that have been occurring in Greece since 2010, based on sequence similarities of viral isolates identified between 2010–2012. However, knowledge on the evolution of this strain is scarce because only partial WNV genome sequences are available from Greece. The aim of this study was to get the complete genome sequence of WNV from patients with infection. To this aim, plasma and urine samples collected during the 2012 Greek outbreak were retrospectively investigated. Full WNV genome sequence was obtained from a patient with WNND. The genome had 99.7% sequence identity to Nea Santa, higher than to other related WNV lineage 2 strains, and five amino acid changes apparently not relevant for viral pathogenicity or fitness. In addition, infection by WNV lineage 2 was confirmed in additional nine patients with WNND; in three of them the infection with WNV Nea Santa was demonstrated by sequencing. In conclusion, this study characterized for the first time a WNV full genome from a patient with WNND from Greece, demonstrated the persistence of the Nea Santa strain, and suggested that the virus might have locally evolved.